The Study of Adherence to Suggestions on Developing Musical Professions of Students Enrolled in Courses Related to Production of Music Artists in Higher Education Institutions in Chiang Mai - Chanteyoon, Ohm; Jaikum, Krerkpong; Subphasri, Poramase (Rangsit Music Journal, 2024)
The purpose of this article are 1) to study the adherence to developing musical professions of students enrolled in courses related to production of music artists in higher education institutions in Chiang Mai, and 2) to suggest ways for the development of a program to recruit personnel in music career fields by using a survey to study the facts based on actual situations. The study's results could conclude that; (1) the overall level of adherence among students were at a high level ( = 4.13, SD=0.09). The level of adherence in the value of music profession was at a high level ( = 4.26, SD=0.24). The level of adherence in the image of the music profession was at a high level ( = 4.14, SD=0.24). The level of adherence in the performance and service of the music profession was at a high level ( = 4.09, SD=0.37). And, the overall level of adherence in studying in fields of music careers was at a high level ( = 4.05, SD=0.22). (2) There are three categories of ways to suggest the development of a program to recruit personnel in the field of music careers: 1) the development of essential skills for students; 2) the preparation of fundamental factors that enhance educational quality; and 3) the implementation of effective and varied extracurricular activities.